(x-6)(x+3)=

Simple and best practice solution for (x-6)(x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-6)(x+3)= equation:


Simplifying
(x + -6)(x + 3) = 0

Reorder the terms:
(-6 + x)(x + 3) = 0

Reorder the terms:
(-6 + x)(3 + x) = 0

Multiply (-6 + x) * (3 + x)
(-6(3 + x) + x(3 + x)) = 0
((3 * -6 + x * -6) + x(3 + x)) = 0
((-18 + -6x) + x(3 + x)) = 0
(-18 + -6x + (3 * x + x * x)) = 0
(-18 + -6x + (3x + x2)) = 0

Combine like terms: -6x + 3x = -3x
(-18 + -3x + x2) = 0

Solving
-18 + -3x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -1x)(6 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6

Solution

x = {-3, 6}

See similar equations:

| -y=0 | | (3a+5)(3a-4)= | | m-9.45=2.7 | | 0=-5y-7x-15 | | -6(-8a-2b+3)= | | 6x+24=8x+16 | | -16x-8=-2y | | 12y-7=19-y | | -3(7+3b)=-6b-3 | | 8d+13=21d | | 3x+5y-11=0 | | 3(3+3x)-2=52 | | 8z^2+32z-az-4a=0 | | -15x^2-115x-150=0 | | (3a-5)(3a+4)= | | 6x+26=2x+144 | | 0=10y-2x+40 | | w^2=27-6w | | 7c+5=6+7c | | 4(2x-2)=8 | | 0=-4x-20-10y | | -3(a-5b-7c)= | | 3x^2-11x-20=0 | | 8st+12t-10s-15=0 | | 86-2x=16x+28 | | 6.5x-2.68=2.6-6.7x | | 2x=y-1 | | 3a+4=3a+2 | | -x+2=0 | | 8-9x=160-37x | | 0.8z=48 | | -18+6x+12m-4x-2m+16= |

Equations solver categories